1999
DOI: 10.1016/s0167-4889(99)00093-2
|View full text |Cite
|
Sign up to set email alerts
|

RGD-CAP (βig-h3) enhances the spreading of chondrocytes and fibroblasts via integrin α1β1

Abstract: In previous studies, RGD-CAP (collagen-associated protein containing the RGD sequence) isolated from a collagen fiber-rich fraction of pig cartilage was found to be orthologous to human (beta)ig-h3, which is synthesized by lung adenocarcinoma cells in response to transforming growth factor-beta. In the present study, we examined the effect of recombinant chick RGD-CAP on the spreading of chondrocytes and fibroblasts using RGD-CAP-coated dishes. When rabbit articular chondrocytes, chick embryonic sternal chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 37 publications
3
63
3
Order By: Relevance
“…The full list of the proteins detected from CAL33 and UM-SCC-1 deroofed cells is provided in supplemental Tables S3 and S4, respectively. Western blots of selected proteins that are known to be involved in tumor progression through their roles in regulating cell-cell adhesion (desmoglein 2 and PG) (41,42), cell-matrix interactions (␤ 4 integrin and ␤Ig-h3) (43)(44)(45), motility and invasion (Rac1) (46), and cell growth and death regulation (␤Ig-h3) (47,48) revealed differential expression and corroborated the mass spectrometry findings (Fig. 4B).…”
Section: Differential Expression Of Basal Cell Proteins In Human Squasupporting
confidence: 73%
“…The full list of the proteins detected from CAL33 and UM-SCC-1 deroofed cells is provided in supplemental Tables S3 and S4, respectively. Western blots of selected proteins that are known to be involved in tumor progression through their roles in regulating cell-cell adhesion (desmoglein 2 and PG) (41,42), cell-matrix interactions (␤ 4 integrin and ␤Ig-h3) (43)(44)(45), motility and invasion (Rac1) (46), and cell growth and death regulation (␤Ig-h3) (47,48) revealed differential expression and corroborated the mass spectrometry findings (Fig. 4B).…”
Section: Differential Expression Of Basal Cell Proteins In Human Squasupporting
confidence: 73%
“…We confirmed that MRC-5 cells express the ␣v␤5 integrin on their cell surface. Ohno et al (9) previously reported that ␤ig-h3 mediates MRC-5 fibroblast cell adhesion through the ␣1␤1 integrin. However, we consistently found that ␣1 and ␤1 integrin-function blocking antibodies did not significantly block MRC-5 cell adhesion to ␤ig-h3.…”
Section: Although D-iv-l D-iv-r D-iv-laa D-iv-aar and D-iv-lyhrmentioning
confidence: 98%
“…Periostin is especially highly homologous to ßig-h3, a member of the fasciclin I family which has been isolated as a transforming growth factor ß (TGF-ß)-responsive gene (7). ßig-h3 promotes cell adhesion and fibroblast spreading via integrin α1ß2 (8,9) and suppresses the ability of Chinese hamster ovary (CHO) cells to develop into tumors in nude mice (10). The expression of periostin is also increased by TGF-ß (1), and periostin mRNA expression is down-regulated by the introduction of Wnt-3 and by the inhibition of glycogen synthase kinase 3ß (GSK-3ß) (11), suggesting that loss of periostin expression could promote oncogenesis.…”
Section: Introductionmentioning
confidence: 99%